Editorial: The power of implicit theories for learning in different educational contexts - Karlen, Yves; Hertel, Silke (Frontiers in education, 2021)
The Power of Implicit Theories for Learning in Different Educational ContextsOver the last few decades, members of the field of (educational) psychology have discussed how implicit theories (or mindsets) about one's abilities build an important "meaning system" that can set different learning trajectories and prime particular learning behaviours. For example, these theories might explain why certain students thrive when facing challenges while others languish. Implicit theories are defined as core assumptions about personal abilities or attributes. They can be characterised along a continuum that ranges from an incremental theory (growth mindset), which maintains that abilities can be developed, to an entity theory (fixed mindsets), which views abilities as relatively fixed and unchangeable. However, due to the increasing attempts to replicate previous effects reported for implicit theories, researchers have paid more attention to the questions of whom, why, and under what conditions the effects of an incremental theory (growth mindset) can be expected (Sisk et al., 2018; Yeager and Dweck, 2020; OECD, 2021).Researchers use questionnaires and alternative assessment methods (e.g., neuroscience, interviews) to understand implicit theories as they apply to different age groups (Mangels et al., 2006; Compagnoni et al., 2019). Thus, paying attention to how and which implicit theories are measured to compare results is important. This is especially important since individuals can simultaneously hold various implicit theories that concern different abilities. For example, implicit theories can address domain-general implicit theories (e.g., intelligence, willpower) or domain- or ability-specific implicit theories (e.g., self-regulated learning, math). Over the last few years, some researchers have argued that domain-specific implicit theories may be better suited for predicting domain-specific behaviour than domain-general implicit theories (Gunderson et al., 2017; Hertel and Karlen, 2021). It might therefore be beneficial to examine both domain-general and domain-specific theories together. Consequently, examining how findings from one domain apply to another is essential. This circumstance calls for studies that aim to replicate previously reported results. Finally, researchers have empirically demonstrated that (short) interventions could change implicit theories (Bostwick and Becker-Blease, 2018; Burnette et al., 2020; Lee et al., 2021). However, the approaches and the effects of those interventions are heterogeneous. One reason for these inconsistent results might be that interventions are likely to be stronger or weaker for different groups and contexts. Therefore, more (intervention) studies that explore the potential for different implicit theories in diverse populations and different cultural contexts and with different approaches must be conducted. The purpose of this Research Topic is to provide an overview of the latest research on implicit theories. We take a multi-perspective view on implicit theories and bring together current research on different implicit theories (see overview in Table 1). This Research Topic includes a total of 14 studies that address implicit theories by using empirical data from samples that were collected from different continents and cultural contexts, including Asia (China and Singapore), Europe (Finland, Germany, Portugal, Switzerland and the United Kingdom) and North America (the United States). Researchers assessed implicit theories in different age groups: starting from kindergarten, researchers studied children in early childhood education (Compagnoni et al.), followed by primary school students (Law et al.; Puusepp et al.; Su et al.), lower and upper secondary students (Karlen et al.; Liu; Wolff) and up to older learners at colleges and universities (Bauer & Hannover; Montagna et al.; Muenks et al.; Yang and Wang). Besides learners, researchers have also examined other groups such as teachers (Rechsteiner et al.) and parents (Levinthal et al.; Stern & Hertel). Several researchers have assessed domain-general implicit theories such as implicit theories about intelligence (Bauer & Hannover; Liu; Montagna et al.; Muenks et al.; Stern & Hertel; Su et al.; Yang & Wang), implicit theories about learning (Levinthal et al.), implicit theories about willpower (Compagnoni et al.) and implicit theories about failure, difficulty, and efforts (Muenks et al.; Su et al.; Stern & Hertel; Yang & Wang). Other researchers have taken a more domain- or ability-specific approach by assessing implicit theories about self-regulated learning (Karlen et al., Stern & Hertel), implicit theories about science and math (Law et al.; Puusepp et al.; Wolff) and implicit theories about school improvement (Rechsteiner et al.). Many researchers have captured implicit theories using questionnaires; however, these questionnaires are marked by differences. While the majority of researchers have empirically assessed implicit theories as one (bipolar) construct, one researcher used a multidimensional scale (Liu) to assess entity and incremental theory separately. A group of researchers who conducted a neuroscience study applied a different approach by providing new insight into implicit theories' neural foundations (Puusepp et al.). Finally, several researchers who have conducted intervention studies have examined whether people can be triggered into adopting different implicit theories in different situations (Bauer & Hannover; Law et al.; Montagna et al.; Puusepp et al.). What lessons were learned from the studies on this Research Topic?How do implicit theories support successful learning?Researchers have found several replicable associations between domain-general and domain-specific implicit theories concerning student learning and performance patterns across different age groups and cultural backgrounds. Additionally, implicit theories, for the most part, relate to students’ learning and motivation, which, in turn, positively affects their academic achievement.For young learners, Compagnoni et al.'s results indicate that Swiss kindergarteners who think of their willpower as a non-limited resource demonstrate better behavioural self-regulation and a higher willingness to exert effort. Su et al. reported that Chinese fifth-graders’ implicit theories about intelligence positively relate to students' beliefs about failure and mathematical self-efficacy, and, in turn, to mathematical achievement. Finally, Puusepp et al. found that Finnish elementary students' implicit theories about math (but not their theories about intelligence) are linked to processing feedback concerning their performance in math, which highlights the importance of domain-specific approaches. Moving to secondary school students, Karlen et al. found a positive relationship between Swiss students' implicit theories about self-regulated learning and their self-concepts, learning emotions, strategy knowledge, and academic achievements. Finally, Lui studied Singapore students' implicit theories about intelligence. Incremental intelligence theory positively relates to mastery-approach goals and, in turn, positively associates with intrinsic motivation and test scores in mathematics. Regarding university students, Muenks et al. examined U.S. undergraduate students' implicit theories. These students' implicit theories (intelligence, effort and failure) predicted their motivations, belonging, and choices of complex (over easy) tasks, even controlling for gender and prior achievements. For another study that originated in the United States, Yang and Wang used person-centred latent profiles to categorise profiles based on different implicit beliefs (ease and difficulty implicit theories and implicit theories about intelligence). They found that students who endorse motivation-increasing implicit theories are more likely to hold mastery-approach goals. However, implicit theories' profiles do not directly relate to strategy use, but goal orientation does. Are there differences between implicit theories in groups of students?We focused on examining if the studies in this Research Topic point out systematic differences between children and students concerning their implicit theories. The results demonstrate that low-achieving kindergartners from Switzerland reported more often that willpower is a limited resource (Compagnoni et al.). Similarly, Swiss secondary school students in lower academic tracks claimed more often that their abilities to self-regulate learning are relatively unchangeable rather than malleable (Karlen et al.). Moreover, several researchers reported gender differences. The results might differ depending on whether an ability is seen as more feminine or masculine (stereotype). For example, Su et al. wrote that Chinese boys have significantly higher mean levels of implicit theories about intelligence and self-efficacy...